Viabilidade polínica e hibridização genômica in situ aplicada ao melhoramento de triticale - Brambatti, Adriana (2010)
Cytogenetic analysis are important tools to an assisted selection strategy in a breeding program, enabling information about the genetic constitution and the materials stability quickly, once to obtain stable plants, several generations are needed because of the genes disintegration. This study aimed, firstly, assess the pollen viability of 29 genotypes of secundary triticale and possibly hexaploid (X Triticosecale Wittmack) belonging to the block of the breeding program of Embrapa Trigo, in 2009, using a randomized block design, with five variables examined in 29 treatments, where in each treatment was made five replications, represented by a tang of a different plant. The other goal was to analyze, by genomic in situ hybridization (GISH), the chromosomal stability in mitotic cells, especially to the presence or absence of translocations in five elite genotypes of the breeding program, using rye genomic DNA as probe. The third objective was to confirm the ploidy level of the materials analyzed by GISH. The pollen viability data were subjected to analysis of variance (ANOVA) and the averages compared by Tukey test at 1%. The correlation data were analysed by Person test. Most of the pollen grains showed a high rate of binucleate/trinucleate (90%), values considered satisfactory. All triticales were hexaploids. About GISH, a genotype showed a possible chromosomal translocations and the other showed a pattern to complete triticale. However, we suggest further studies to see which of wheat genomes and chromosomes were involved in the translocations. We concluded that, tested materials were stable about the polinic viability and the ploidy level. The presence of chromosomal translocation in mitotic cells does not represent a heritable genotypic instability, because it is only proven by studies on meiotic cells